1990
DOI: 10.1007/bf01658686
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic segmentectomy with caudate lobe resection for bile duct carcinoma of the hepatic hilus

Abstract: From 1979 through 1989, surgical resection was performed in 55 of 66 patients with carcinoma of the hepatic hilus after improving jaundice by percutaneous transhepatic biliary drainage (PTBD). Selective cholangiography through PTBD was done to define precisely the anatomical location--extent of the obstructing lesion in each segmental hepatic duct. Percutaneous transhepatic cholangioscopy was performed through the sinus tract of PTBD after replacing the drainage catheter with a 15 French catheter for supersele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
332
2
8

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 460 publications
(351 citation statements)
references
References 30 publications
(37 reference statements)
9
332
2
8
Order By: Relevance
“…(Grade 1, evidence level B) Statement: Bile ducts of caudate lobe confluent into the bifurcation of left and right bile duct. These branches are frequently invaded by hilar/upper bile duct carcinoma [138][139][140][141]. According to these facts, some reports describe that the combined caudate lobe resection should be designed so that curative surgery for advanced hilar bile duct carcinoma can be performed [141].…”
Section: Cq16: What Are Considered As Unresectable Factors In Biliarymentioning
confidence: 99%
“…(Grade 1, evidence level B) Statement: Bile ducts of caudate lobe confluent into the bifurcation of left and right bile duct. These branches are frequently invaded by hilar/upper bile duct carcinoma [138][139][140][141]. According to these facts, some reports describe that the combined caudate lobe resection should be designed so that curative surgery for advanced hilar bile duct carcinoma can be performed [141].…”
Section: Cq16: What Are Considered As Unresectable Factors In Biliarymentioning
confidence: 99%
“…2,15,16 In the present study, we observed a 16% 5-year survival rate.These poor results could be due to late diagnoses and presences of liver cirrhosis in 46% of our patients Since the first successful liver and bile duct resection for the treatment of HCCA, there has been a debate about the extent of resection (localized or extensive). 11,[17][18][19] In our experience, skeletonization resection of the extrahepatic biliary system is rarely sufficient to ensure radical treatment of the tumor because it must be combined with liver resection and even with caudate resection and biliary anastomosis in the first and second order ducts of the residual liver. In this study, 30.5% of patients underwent localized resection and 69.5% underwent major resection with median survival rates of 18 and 22 months, respectively, with no significant differences between the two groups (P<0.106) these results are similar to those observed in some studies 20 and contrary to those in other reports.…”
Section: Discussionmentioning
confidence: 98%
“…Better prognoses have been shown to be associated with resection rather than with palliative treatment. [10][11][12][13][14] In our study, in those patients who underwent laparotomy and had tumors that were underestimated at the preoperative evaluation, such as those exhibiting peritoneal and or metastatic spread, palliative treatment in the form of biliary decompression was obtained by different methods (transmural drainage and surgical endoprothesis). Infiltration of the portal vein (main trunk or bifurcation without vascular thrombosis) or involvement of the local or locoregional lymph nodes and/or the adjacent liver are not absolute contraindications for resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A preoperative bilirubin level lower than 3 mg/dl has been recommended by Makuuchi et al [39] and Nimura et al [40], thus suggesting an important role of PBD in managing HC. A recent single center retrospective study [41] reviewed a 10 years' experience of 105 patients treated for HC.…”
Section: Preoperative Bilirubin Levelmentioning
confidence: 99%